2019
DOI: 10.48550/arxiv.1908.10319
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Carbon, oxygen, and iron abundances in disk and halo stars. Implications of 3D non-LTE spectral line formation

A. M. Amarsi,
P. E. Nissen,
Á. Skúladóttir

Abstract: The abundances of carbon, oxygen, and iron in late-type stars are important parameters in exoplanetary and stellar physics, as well as key tracers of stellar populations and Galactic chemical evolution. However, standard spectroscopic abundance analyses can be prone to severe systematic errors, based on the assumption that the stellar atmosphere is one-dimensional (1D) and hydrostatic, and by ignoring departures from local thermodynamic equilibrium (LTE). In order to address this, we carried out three-dimensio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 66 publications
2
9
0
Order By: Relevance
“…The left panels show for both the thin and thick disk stars a large scatter in the [C/H] values. Such a scatter was also found by Nissen & Gustafsson (2018); Amarsi et al (2019c) and they suggested that it can be explained by variations in the dust to gas ratio in different star-forming gas clouds and/or by the need of applying differential 3D non-LTE corrections to 1D LTE abundances (see discussion at the end of Section 2.2.2).…”
Section: Chemical Properties Of the Thin And Thick Disk Star Samplessupporting
confidence: 53%
See 2 more Smart Citations
“…The left panels show for both the thin and thick disk stars a large scatter in the [C/H] values. Such a scatter was also found by Nissen & Gustafsson (2018); Amarsi et al (2019c) and they suggested that it can be explained by variations in the dust to gas ratio in different star-forming gas clouds and/or by the need of applying differential 3D non-LTE corrections to 1D LTE abundances (see discussion at the end of Section 2.2.2).…”
Section: Chemical Properties Of the Thin And Thick Disk Star Samplessupporting
confidence: 53%
“…Amarsi et al 2019a). The paper by Amarsi et al (2019c) shows that in the metallicity regime of our stars ([Fe/H]> −1) the 3D-NLTE corrections do not change significantly the [C/Fe] ratios (see their Figure 11). Their paper provides, in any case, a tool to correct 1D-LTE carbon abundances to take into account the 3D-NLTE effects.…”
Section: [C/fe] Determinationmentioning
confidence: 61%
See 1 more Smart Citation
“…Using Ni+Tr/2 gives 19%, perhaps on the low side. Observationally the fraction of iron from core-collapse supernovae, based on measurements of O/Fe or α/Fe (where α may be Mg, Si, S, Ca, or Ti), is usually thought to be about 1/4-1/3 (e.g., Fulbright et al 2007;Barbuy et al 2018;Amarsi et al 2019), though some recent observations suggest it may be as large as 50% (Griffith et al 2019). Taking 0.073 for 0.75×(Ni+Tr+a) increases the maximum average 56 Ni production for W18 and raises the fraction to 33% which is also acceptable.…”
Section: Nucleosynthesismentioning
confidence: 99%
“…6 we display different datasets in the [C/Fe]-[Fe/H] and [C/Mg]-[Mg/H] planes (top and bottom panels, respectively). The red and blue symbols refer to abundance measurements from highresolution, high signal-to-noise ratio (SNR) spectra of single thin-and thick-disc stars, respectively, presented in Bensby and Feltzing (2006), Bensby et al (2014), Nissen and Schuster (2010), Nissen et al (2014), Amarsi et al (2019). The solid red and blue lines represent the average trends derived by Franchini et al (2020) from, respectively, about 1300 thin-disc and nearly 100 thick-disc dwarf stars from the fifth internal data release of GES (GES iDR5).…”
Section: The Milky Way Galaxymentioning
confidence: 99%